L-ARGININE MITIGATES HEAVY METAL INHIBITED NITRIC OXIDE SYNTHASE ACTIVITY IN TISSUES OF THE ALBINO RAT - KUMAR, C. ASHOKA; KUMAR, K. M. UDAY; KUMARI , K. VIJAYA; RAO, M. RAJESWARA (The Bioscan, 2012)
Nitric oxide (NO) is synthesized endogenously by the enzymes NO synthase (NOS) and NO is well known to act as physiologic messenger in the body. Heavy metals induce number of toxic effects in animals including man. Keeping in view the important biologic roles played by NO and toxic effects exerted by heavy metals, the in vitro effects of selected heavy metals like mercury (Hg), lead and the amino acid L-arginine separately and in combination was studied on the rat tissue NOS activity. The results indicated, Hg2+ and Pb2+ in concentrations of 10-1000 µM inhibited rat major tissues cNOS and iNOS activities and that L-arginine at selected concentration of 10-20 µM appeared to reverse the IC50 conc. Of heavy metal inhibited rat tissue NOS activity levels in vitro. It is reported that L-arginine as it acts as a substrate to NO production, its supplementation may improve the NOS disorders in experimental animals.